2015
DOI: 10.1021/acs.jcim.5b00106
|View full text |Cite|
|
Sign up to set email alerts
|

Force Field Benchmark of Organic Liquids. 2. Gibbs Energy of Solvation

Abstract: Quantitative prediction of physical properties of liquids is a longstanding goal of molecular simulation. Here, we evaluate the predictive power of the Generalized Amber Force Field (Wang et al. J. Comput. Chem. 2004, 25, 1157-1174) for the Gibbs energy of solvation of organic molecules in organic solvents using the thermodynamics integration (TI) method. The results are compared to experimental data, to a model based on quantitative structure property relations (QSPR), and to the conductor-like screening mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
146
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(152 citation statements)
references
References 83 publications
3
146
0
Order By: Relevance
“…Our findings that chloroform solvation free energies have the largest errors to experiment, despite reasonable correlation for GAFF, are consistent with the recent results of Zhang et al36 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings that chloroform solvation free energies have the largest errors to experiment, despite reasonable correlation for GAFF, are consistent with the recent results of Zhang et al36 …”
Section: Discussionsupporting
confidence: 93%
“…This study showed good agreement (<1.0 kcal mol −1 ) of solvation free energies with experiment, albeit in four related polar solvents and three related nonpolar solvents 35. In a larger study, Zhang et al compared the performance of GAFF with three different prediction methodologies for solvation free energies (thermodynamic integration, a quantitative structure‐property relationship [QSPR] and the conductor‐like screening model for realistic solvation [COSMO‐RS]), employing a wide range of organic solvents 36. These studies involved the evaluation of Gibbs solvation free energies for 228 organic molecules in organic solvents compared against experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The recent reported work of Zhang et al 31 also examined solvation free energies in non-aqueous solvents, comparing alchemical techniques with an empirical technique based on quantitative structure property relations, and quantum mechanical calculations with COSMO-RS. It found that the alchemical approach was not a clear winner, with the other two models in fact performing slightly better.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that this may be precisely because of the relative abundance of solubility data compared to solvation free energy data. Specifically, the QSPR and COSMO-RS methods employed by Zhang et al 31 have both been specifically fit at least in part to reproduce solvation free energies, and given the relatively small amount of solvation free energy data available, their training may have involved some of the same compounds on which they were tested. In contrast, the vast amount of solubility data available – and the lack of training of the methods tested on solubility data – means that the present test gives less of an advantage to empirical or semi-empirical methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation